Dynamics of the ice cap on King George Island, Antarctica - field measurements and numerical simulations - Braun, Matthias; et al. (Annals of Glaciology, 2010)
King George Island is located at the northern tip of the Antarctic Peninsula, which is influenced by maritime climate conditions. The observed mean annual air temperature at sea level is-2.47deg;C. Thus, the ice cap is regarded as sensitive to changing climatic conditions. Ground-penetrating radar surveys indicate a partly temperate ice cap with an extended water layer at the firn/ice transition of the up to 700 m high ice cap. Measured firn temperatures are close to 0°C at the higher elevations, and they differ considerably from the measured mean annual air temperature. The aim of this paper is to present ice-flow dynamics by means of observations and simulations of the flow velocities. During several field campaigns from 1997/98 to 2008/09, ice surface velocities were derived with repeated differential GPS measurements. Ice velocities vary from 0.7 m a-1 at the dome to 112.1 m a-1 along steep slopes. For the western part of the ice cap a three-dimensional diagnostic full-Stokes model was applied to calculate ice flow. Parameters of the numerical model were identified with respect to measured ice surface velocities. The simulations indicate cold ice at higher elevations, while temperate ice at lower elevations is consistent with the observation
UnivIS-Import:2015-04-20:Pub.2010.nat.dgeo.IG.pgfgis.dynami